Pengaruh Ukuran Perusahaan, Likuiditas Dan Profitabilitas Terhadap Kinerja Keuangan Dengan Kesehatan Modal Sebagai Variabel Intervening Pada Bank Syariah Indonesia.Tbk Tahun 2021-2024 - Hakim Muttaqim; Tri Ratnawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of firm size, liquidity, and profitability on financial performance, with capital adequacy as an intervening variable. The focus of this study is Bank Syariah Indonesia Tbk. The research data were obtained from the bank’s quarterly published financial reports during the 2021–2024 period. A quantitative approach was employed using Partial Least Squares (PLS) analysis techniques. The data analyzed include financial statements encompassing firm size (total assets, financing distribution), liquidity (fundraising, Financing to Deposit Ratio/FDR), profitability (Return on Assets/ROA, net income), financial performance (Non-Performing Financing/NPF, Operational Efficiency Ratio/BOPO), and capital adequacy (equity, Return on Equity/ROE). The results indicate that firm size, liquidity, profitability, and capital adequacy have no significant effect on the financial performance of Bank Syariah Indonesia Tbk, either directly or through mediation. All hypotheses were rejected, suggesting that the variables under study were not sufficient to explain the variations in financial performance. Limitations related to the data period, the bank's relatively recent establishment, and external factors such as macroeconomic conditions and regulatory frameworks are presumed to be the main contributing factors.